Country-Specific Preferences and Employment Rates in Europe - Simone Moriconi; Giovanni Peri (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2015)
European countries exhibit significant differences in employment rates of adult males. Differences in labor-leisure preferences, partly determined by cultural values that vary across countries, can be responsible for part of these differences. However, differences in labor market institutions, productivity, and skills of the labor force are also crucial factors and likely correlated with preferences. In this paper we use variation among first- and second-generation cross-country European migrants to isolate the effect of culturally transmitted labor-leisure preferences on individual employment rates. If migrants maintain some of their country of origin labor-leisure preferences as they move to different labor market conditions, we can separate the impact of preferences from the effect of other factors. We find country-specific labor-leisure preferences explain about 24per cent of the top-bottom variation in employment rates across European countries.
Keywords: J22; J61; Z10; 330; Labor-Leisure Preferences; Cultural Transmission; Employment; Europe; Migrants